Smallholder Farmers’ perceptions of climate change and adaptation strategies in Southern Ethiopia: Mixed method approach - Negussie Zeray (Climate Services)
The study objective is to assess farmers’ perception and adaptation to climate change in the Karat Zuria district, Southern Ethiopia. Multivariate probit models and descriptive statistics were used to evaluate cross-sectional data collected from 339 sample households. Surveyed farmers in Karat Zuria largely perceive increasing climate change impacts, including unpredictable rainfall, heat-related crop and animal diseases, intensified weed infestations, rising temperatures, shorter rainy seasons, and worsening droughts/water shortages. 46.4%, 72.5%, 63.4%, 88.9%, 85.6%, 51.0%, and 88.9% of the smallholder farmers’ adaptation strategies to climate change are small-scale irrigation, agro-forestry, changing planting dates, soil and water conservation, growing different types of plants, growing different crop varieties, and using improved fodder crops and hay for livestock feed. The results of the multivariate probit model revealed that the main factors influencing households’ decisions to choose different adaptation strategies for coping with climate change are sex, age, knowledge of climate change, farm income, the number and size of animals owned by the household, the size of the farm, the use of credit, the distance between the farm and the residence, the frequency of drought, and experience of crop loss. To improve climate change adaptation in Karat Zuria, policymakers should focus on tailored interventions that address credit access, agricultural knowledge, and resource management, considering farmers’ unique needs and circumstances.Practical implicationsThe images listed below were all taken when the study’s fieldwork was being done. Images 1 and 6 show rivers, springs, and irrigation water sources that are utilized to gather water and adapt to climate change.As a consequence of key informant interviews and field observations, early maturing crop varieties such as BH140 maize, DZ-CE37 teff, humara-1 sesame, Mung bean, common bean, Gubeye, Asnakech, and Berhane are being used as alternative sorts of adaptation techniques in the research region (See photos 7–17).Since they lessen the risk of flooding and improve soil moisture and organic matter retention, soil and water conservation techniques, notably tracing, are a well-known approach for dealing with climate change. Regarding the agroforestry option, farmers in the study region cultivate fodder plants and widely utilized agroforestry techniques in the neighborhood include the indigenous Oybata (Terminalia browine) and pigeam pea (Cajanus cajan).In order to alleviate the shortage of animal feed, farmers frequently plant indigenous forage (Kanda), Rhodes grass (Chloris gayana), and elephant grass (Pennisetum purpureum) around their fields. On the other hand, farmers in the study area frequently feed their animals agricultural leftovers and harvest acacia pods during times of drought as a kind of adaptation to climate change.